Impact of Gastrointestinal Symptoms on Health-Related Quality of Life in an Australian Parkinson’s Disease Cohort - Jade E. Kenna; Megan C. Bakeberg; Maddison Y. Abonnel; Frank L. Mastaglia; Ryan S. Anderton (Parkinson's Disease)
Background. Gastrointestinal symptoms (GIS) in people with Parkinson’s disease (PwP) are often underreported and may remain untreated. Constipation is a common nonmotor symptom that can adversely affect health-related quality of life (QoL); however, the impact of other GIS has not been adequately investigated. Objectives. To investigate the relationship between QoL and constipation using the Bristol Stool Chart, bowel movement frequency, and a perceived constipation measure; and to explore the relationship between QoL and other GIS in an Australian PD cohort. Methods. The impact of constipation and other GIS on QoL, as measured using the PDQ-39 scale, was assessed in a cohort of 144 (89 males, 55 females) clinic-attending PwP. Constipation was assessed using the Bristol Stool Chart as well as a composite constipation measure, and the Gastrointestinal Symptom Rating Scale (GSRS) was used to rate other GIS. Covariate corrected linear regression models were utilised to determine significant associations between GIS and QoL scores. Results. Individual and combined constipation measures were significantly associated with poorer QoL (p=0.032 and p=0.002, respectively). Analysis of GSRS symptom domains showed that in addition to symptoms of gastrointestinal hypomotility, a number of other symptoms such as increased eructation and increased flatus were also associated with poorer QoL. Conclusions. The findings point to the importance of GIS as contributor to health-related QoL in PwP. A better understanding of the relationship between GIS and QoL will help facilitate the development of more effective screening and treatment programs to improve symptom management and QoL for PwP.